Complete mitochondrial genome of the Korean endemic species Microphysogobio yaluensis (Teleostei, Cypriniformes, Cyprinidae). (2nd September 2016) - Park, Chang Eon; Park, Gun-Seok; Kim, Min-Chul; Kim, Kgu-Hwan; Park, Hee Cheon; Lee, In-Jung; Shin, Jae-Ho
Abstract: In this study, we sequenced the complete mitochondrial genome of the Korean endemic species Microphysogobio yaluensis (Teleostei, Cypriniformes, Cyprinidae). The mitogenome, consisted of 16 601 base pairs (bp), encoding 13 protein-coding genes (PCGs), 2 ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs) and 2 non-coding regions. The overall base composition of M. yaluensis was G + C: 43.8%, A + T: 56.2%, apparently with a slight AT bias. Phylogenetic analysis showed that M. yaluensis was close to Hemibarbus mylodon .